2018
DOI: 10.17582/journal.aavs/2019/7.3.187.192
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Trails Associated with Different Doses of Alpha-Monolaurin in Chicks

Abstract: A huge global population growth required enough dietary sources (particularly proteins) to meet the progressing demands. Consequently, poultry production advanced rapidly in many countries over the world (Scanes, 2007). On the other hand, European Union was excluded antibiotic growth promoters (AGPs) in animal foods as an attempt to overcome devastating antibiotic resistance issue (Castanon, 2007), but antibiotic residual in meat was still considered a dominant risk and challenge for both poultry producers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…In the present study, we observed that inclusion of 300 to 600 mg/kg MG in diets led to a notable increase in feed intake and BW gain in broilers during the finisher phase. These results were consistent with those of previous studies in which broilers fed diets containing GML showed significant increased feed consumption and BW at the end of the experiment ( Mustafa, 2018 ; Fortuoso et al., 2019 ). Feed intake is the primary factor driving the growth rate of broilers ( Abdollahi et al., 2018 ), thus significantly increased ADFI induced by MG supplementation was considered to be the main reason for the improvement of growth performance in broilers in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we observed that inclusion of 300 to 600 mg/kg MG in diets led to a notable increase in feed intake and BW gain in broilers during the finisher phase. These results were consistent with those of previous studies in which broilers fed diets containing GML showed significant increased feed consumption and BW at the end of the experiment ( Mustafa, 2018 ; Fortuoso et al., 2019 ). Feed intake is the primary factor driving the growth rate of broilers ( Abdollahi et al., 2018 ), thus significantly increased ADFI induced by MG supplementation was considered to be the main reason for the improvement of growth performance in broilers in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, medium-chain α-monoglycerides ( MG ) are regarded as promising feed supplements for broilers production. Many recently published literatures document that dietary glycerol monolaurate ( GML ) (C12:0) increases BW and feed efficiency, promotes health, and improves meat quality in broilers ( Mustafa, 2018 ; Fortuoso et al., 2019 ; Valentini et al., 2020 ). However, little is known about the effect of dietary glycerol monodecanoate ( GMD ) (C10:0) and glycerol monocaprylin (C8:0) in the diet of broilers till now.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results from Fortuoso et al [13], GML supplementation increase the average body weight, feed consumption and carcass yield in male Cobb 500 broilers without toxic side effect. Likewise, broilers fed diet containing GML show improvements on body weight gain, feed efficiency, immunological and nutritional status in Ross 308 broilers [14]. Our laboratory demonstrated that dietary GML could improve reproductive performance, egg quality and feed efficiency in Hy-Line Brown laying hens during 44-52 weeks of age [15,16].…”
Section: Introductionmentioning
confidence: 79%
“…According to Wang and Kim [20], dietary caprylic acid improved average egg weight and feed efficiency in Hy-Line brown, and had positive effects on serum blood metabolism and health status. Dietary GML supplementation increased body weight, feed consumption and carcass yield, and decreased the FCR in the broiler, which were also better for the health of chicken [13,14]. Dietary fat, rich in free lauric acids improved the FCR and breast muscle yield in broilers [21].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation